2003
DOI: 10.1046/j.1432-1033.2003.03520.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen control of nif gene expression in Klebsiella pneumoniae depends on NifL reduction at the cytoplasmic membrane by electrons derived from the reduced quinone pool

Abstract: In Klebsiella pneumoniae, the flavoprotein, NifL regulates NifA mediated transcriptional activation of the N 2 -fixation (nif) genes in response to molecular O 2 and ammonium. We investigated the influence of membrane-bound oxidoreductases on nif-regulation by biochemical analysis of purified NifL and by monitoring NifA-mediated expression of nifH¢-¢lacZ reporter fusions in different mutant backgrounds. NifL-bound FAD-cofactor was reduced by NADH only in the presence of a redox-mediator or inside-out vesicles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 64 publications
(100 reference statements)
1
40
0
Order By: Relevance
“…Inhibition of Ti plasmid conjugative transfer by TraM joins a growing list of prokaryotic regulatory systems involving an activator-antiactivator complex, including NifA-NifL regulation of nitrogen fixation in Azotobacter vinelandii (33) and Klebsiella pneumoniae (34), ComK-MecA-ClpC regulation of competence in Bacillus subtilis (35), GcvA-GcvR regulation of oxidative cleavage of glycine (36), and CRP-CytR regulation of many operons in E. coli (37). In the cases of NifA-NifL and ComKMecA, the antiactivator binds to and titrates the activator, thus preventing DNA binding and transcriptional activation (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Ti plasmid conjugative transfer by TraM joins a growing list of prokaryotic regulatory systems involving an activator-antiactivator complex, including NifA-NifL regulation of nitrogen fixation in Azotobacter vinelandii (33) and Klebsiella pneumoniae (34), ComK-MecA-ClpC regulation of competence in Bacillus subtilis (35), GcvA-GcvR regulation of oxidative cleavage of glycine (36), and CRP-CytR regulation of many operons in E. coli (37). In the cases of NifA-NifL and ComKMecA, the antiactivator binds to and titrates the activator, thus preventing DNA binding and transcriptional activation (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of NifA-NifL and ComKMecA, the antiactivator binds to and titrates the activator, thus preventing DNA binding and transcriptional activation (33)(34)(35). However in the cases of GcvA-GcvR and CRP-CytR, the antiactivator and the activator bind promoter DNA in tandem, and the interactions between the antiactivator and the activator at the promoter inhibit transcriptional activation (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction potential for NifL (-196 mV, pH 7) is accessible to a number of potential electron donors (41). In Klebsiella pneumoniae, the respiratory quinone pool is thought to be a source of electron donors for NifL (23,73). In order for NifL to be reduced by the quinone pool, NifL is proposed to shuttle between the membrane and the cytoplasm in K. pneumoniae (73).…”
Section: Nifl (Transcriptional Regulator Of Nitrogen Fixation)mentioning
confidence: 99%
“…However, upon anaerobiosis and simultaneous absence of combined nitrogen, the flavoprotein NifL is sequestered to the cytoplasmic membrane (21,54). This membrane sequestration of the negative regulator NifL, allowing cytoplasmic NifA to induce nif gene expression by activating the alternative 54 RNA-polymerase (16,41), is the key mechanism for regulating nitrogen fixation in K. pneumoniae in response to the environmental signals (12,21). In previous studies we obtained evidence that membrane sequestration of NifL under nitrogen-fixing conditions is achieved by the reduction of the N-terminally bound FAD cofactor by electrons derived from the reduced menaquinone pool (11,12,55).…”
mentioning
confidence: 99%
“…This membrane sequestration of the negative regulator NifL, allowing cytoplasmic NifA to induce nif gene expression by activating the alternative 54 RNA-polymerase (16,41), is the key mechanism for regulating nitrogen fixation in K. pneumoniae in response to the environmental signals (12,21). In previous studies we obtained evidence that membrane sequestration of NifL under nitrogen-fixing conditions is achieved by the reduction of the N-terminally bound FAD cofactor by electrons derived from the reduced menaquinone pool (11,12,55). Using partial anaerobic respiratory chains of Wolinella succinogenes reconstituted in liposomes further demonstrated that under anaerobic conditions electrons are directly transferred from the menaquinol pool onto NifL-bound FAD without the requirement for any further K. pneumoniae specific protein (e.g., receptor proteins or NifL-specific oxidoreductases).…”
mentioning
confidence: 99%